Retinal ganglion cell distribution and visual acuity in alpacas (Vicugna pacos) - Wang, Hsiao-Hui, author; Madl, James, advisor; Gionfriddo, Juliet, advisor; Byers, Stacey, committee member; Vigh, Jozsef, committee member (Colorado State University. Libraries, 2013)
Vision reflects the visual demand for environmental adaptation of an animal and also implies the biological niche of a species. Retinal specializations, such as visual streaks, areae centrales and foveae, have been found in animals and the function of each retinal specialization is correlated to its visual needs. Harman et al analyzed retinal ganglion cell (RGC) topography of dromedary camels and found a vertical steak which is unusual for ungulates. A vertical steak had only been reported in two-toed sloths. Because alpacas are closely related to dromedary camels in the same taxonomic family, we hypothesized that alpacas have similar RGC topography as do dromedary camels rather than other grazing animals. Five healthy alpaca eyes were included in the current study. Anti-Brn-3a antibody was used to label the RGCs and 25% of the retinal area was imaged to quantify the RGCs. Two other RGC staining techniques, Lucifer Yellow retrograde labeling and cresyl violet staining, were attempted but failed. A topographic retinal map of RGC densities was reconstructed based on the RGC counts. The axial length of each eye was measured and the measurement was used to calculate the visual acuity of alpacas. The results of the Brn-3a labeling showed that alpacas have a horizontal streak across the retinal meridian superior to the optic disc with an upward extension at the temporal end of the streak. The highest RGC density area of the five retinas was in the temporal region. The maximal visual acuity, located in the temporal retina, ranged between 12.5 and 13.4 cycles per degree. Based on the results, we concluded that the RGC topography of alpacas was similar to that of other grazing animals, such as ox, sheep and horses, rather than that of dromedary camels.
Keywords: alpaca; Brn-3a; camelid; retinal ganglion cell; topography; visual acuity